Manufacturing process optimization of self-sealing safety tire [electronic resource] - Gu Shuai, 1983-; Norizah Redzuan, supervisor; Fakulti Kejuruteraan Mekanikal (2014)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2014